Influence of Teachers’ Grouping Strategies on Children’s Peer Social Experiences in Early Elementary Classrooms - Kim, Saetbyul; Lin, Tzu-Jung; Chen, Jing; Logan, Jessica; Purtell, Kelly M.; Justice, Laura M. (Frontiers in Psychology, 2020)
Most children experience some form of grouping in the classroom every day. Understanding how teachers make grouping decisions and their impacts on children’s social development can shed light on effective teacher practices for promoting positive social dynamics in the classroom. This study examined the influence of teachers’ grouping strategies on changes in young children’s social experiences with peers across an academic year. A total of 1,463 children (51% girls, Mage = 6.79, SDage =1.22) and 79 teachers from kindergarten to third-grade classrooms participated in this study. Teachers rated children’s behavioral problems as the most important consideration when creating seating charts or assigning children to small groups. Promoting existing or new friendships was rated as the least important consideration. Heterogeneous ability grouping, rated as somewhat important by the teachers, was associated with a decrease in children’s friendships and yet also a decrease in girls’ experience with peer conflicts. Our findings begin to fill in the gaps in the literature on the social impacts of ability grouping for young children.